Ventromedial Hypothalamus Activation Aggravates Hypertension Myocardial Remodeling Through the Sympathetic Nervous System - Zhou, Yuyang; Liu, Zhihao; Liu, Zihan; Zhou, Huixin; Xu, Xiao; Li, Zeyan; Chen, Hu; Wang, Yuhong; Zhou, Zhen; Wang, Meng; Lai, Yanqiu; Zhou, Liping; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The ventromedial hypothalamus (VMH) is an important nuclei in emotional stress, which is a risk factor for cardiovascular diseases. However, the role of the VMH in cardiovascular diseases remains unknown. This study aimed to investigate the effects and underlying mechanisms of VMH activation on hypertension related cardiac remodeling in two-kidney-one-clip (2K1C) hypertension (HTN) rats. Methods: Eighteen male Sprague-Dawley rats were injected with AAV-hSyn-hM3D(Gq) into the VMH at 0 weeks and then randomly divided into three groups:1) sham group (sham 2K1C + saline i.p. injection); 2) HTN group (2K1C + saline i.p. injection); 3) HTN+VMH activation group (2K1C + clozapine-N-oxide i.p. injection). One week later, rats were subjected to a sham or 2K1C operation, and 2 weeks later rats were injected with clozapine-N-oxide or saline for 2 weeks. Results: In the HTN+VMH activation group, FosB expression was significantly increased in VMH sections compared with those of the other two groups. Compared to the HTN group, the HTN+VMH activation group showed significant: 1) increases in systolic blood pressure (SBP) and decreases in left ventricular ejection fraction and fractional shortening; 2) exacerbation of cardiac remodeling; and 3) increases in serum norepinephrine levels and sympathetic indices of heart rate variability. Additionally, myocardial RNA-sequencing analysis showed that VMH activation might regulate the HIF-1 and PPAR signal pathway and fatty acid metabolism. qPCR results confirmed that the relative mRNA expression of HIF-1α was increased and the PPARα and CPT-1 mRNA expression were decreased in the HTN+VMH activation group compared to the HTN group. Conclusions: VMH activation could increase SBP and aggravate cardiac remodeling possibly by sympathetic nerve activation and the HIF-1α/PPARα/CPT-1 signaling pathway might be the underlying mechanism.